2003
DOI: 10.1016/s0014-5793(03)01344-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pollen‐expressed pectin methylesterase inhibitors in Arabidopsis

Abstract: Pectin methylesterases (PMEs) play an essential role during plant development by a¡ecting the mechanical properties of the plant cell wall. Previous work indicated that plant PMEs may be subject to post-translational regulation. Here, we report the analysis of two proteinaceous inhibitors of PME in Arabidopsis thaliana (AtPMEI1 and 2). The functional analysis of recombinant AtPMEI1 and 2 proteins revealed that both proteins are able to inhibit PME activity from £owers and siliques. Quantitative RT-PCR analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 21 publications
3
105
0
Order By: Relevance
“…Four PMEIs have been functionally characterized in Arabidopsis to date. PMEI1 and PMEI2 (Wolf et al, 2003) are highly expressed in flowers; PMEI1 expression is specific to pollen, while the expression of PMEI3 is particularly high in the apical meristem (Peaucelle et al, 2008). PMEI4 is up-regulated during growth acceleration in skotomorphic hypocotyls (Pelletier et al, 2010).…”
Section: Oe Of a Novel Pmei As A System To Study Pme Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Four PMEIs have been functionally characterized in Arabidopsis to date. PMEI1 and PMEI2 (Wolf et al, 2003) are highly expressed in flowers; PMEI1 expression is specific to pollen, while the expression of PMEI3 is particularly high in the apical meristem (Peaucelle et al, 2008). PMEI4 is up-regulated during growth acceleration in skotomorphic hypocotyls (Pelletier et al, 2010).…”
Section: Oe Of a Novel Pmei As A System To Study Pme Functionmentioning
confidence: 99%
“…The first described PMEI was that purified from kiwifruit (Actinidia chinensis; Balestrieri et al, 1990), and since then, several PMEIs from Arabidopsis (Arabidopsis thaliana) and other plant species have been characterized (Wolf et al, 2003;Raiola et al, 2004). Individual PMEIs interact with a number of different PMEs, often even over species boundaries .…”
mentioning
confidence: 99%
“…Four of the significantly down-regulated genes are pollen specific (Honys and Twell 2004). Among them, At1g48020 (AtPMEI1) (Wolf et al 2003) was suppressed 11.6 fold, At2g07040 10.0 fold, Profilin 5 (At2g19770) 4.8 fold, and At2g43230 4.3 fold respectively. APG (At1g20130), which is suppressed 7.6 fold, is an antherspecific gene expressed during the period of microspore development in B. napus buds and flowers (Roberts et al 1993).…”
Section: Verification Of Expression Pattern Using Rt-pcrmentioning
confidence: 99%
“…In addition to the transcriptional control, a mechanism of regulation of PME activity is played by specific proteinaceous inhibitors, which were discovered in kiwi (Actinidia deliciosa) (Balestrieri et al, 1990;Giovane et al, 1995) and recently found also in Arabidopsis thaliana (Wolf et al, 2003;Raiola et al, 2004). These inhibitors, named PMEIs, typically inhibit PMEs of plant origin and do not affect the activity of microbial enzymes .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that PMEs and PMEIs are both expressed in flower tissues and pollen grains (Wolf et al, 2003;Markovic and Janecek, 2004;Raiola et al, 2004;L. Camardella, A. Giovane, and D. Bellincampi, unpublished results) and that wind and animal visitations continually bring pollen onto flowers 1 Current address: Dipartimento del Territorio e Sistemi Agro-Forestali, Università di Padova, Italy.…”
Section: Introductionmentioning
confidence: 99%